IMPLIKASI PENERAPAN UNDANG-UNDANG NOMOR 6 TAHUN 2023 TENTANG CIPTA KERJA DALAM PENGATURAN KAWASAN HUTAN UNTUK PEMBANGUNAN PROYEK STRATEGIS NASIONAL (STUDI KASUS BENDUNGAN TEFMO-MANIKIN DI KABUPATEN KUPANG–PROVINSI NTT) - Agustina, Agustina; Pello, Jimmy; Manuain, Orpa G (Petitum Law Journal, 2023)
The issuance of Law Number 6 of 2023 concerning Job Creation has had an impact on changes to a number of laws in Indonesia, including Law Number 19 of 2004 concerning Forestry and Law Number 2 of 2012 concerning Land Acquisition for Development in the Public Interest. In addition, derivative regulations from the Job Creation Law, especially those relating to support for facilitating the development of National Strategic Projects, have been issued after the ratification of Law Number 11 of 2020 concerning Job Creation. The derivative regulations in question are Government Regulation Number 23 of 2021 concerning Forestry Implementation and Government Regulation Number 42 of 2021 concerning Facilitation of National Strategic Projects. The presence of the Job Creation Law is considered to be able to encourage economic growth, one of which is by accelerating the development of strategic infrastructure in the regions. The research method used is normative juridical. The results of this research show that the presence of the Job Creation Law has had an impact on simplifying and trimming a number of regulations to facilitate and support the accelerated development of National Strategic Projects including the Tefmo – Manikin Dam in Kupang Regency. On the one hand, the passing of Law Number 6 of 2023 concerning Job Creation has provided a guarantee of legal certainty, because so far the process has experienced pros and cons. However, in terms of legal benefits and environmental justice, it can result in disruption of environmental sustainability, especially forest areas because they are vulnerable to conversion of forest areas for the development of National Strategic Projects.